Hepatocellular carcinoma in cirrhotic liver CT an MRI findings - Castrillón, Germán (Iatreia, 2007)
For all practical purposes, you should consider cirrhosis to be a pre-malignant condition. This means that a patient with cirrhosis is at risk for developing hepatocellular carcinoma (HCC). The greater or lesser risk depends on the etiology of the cirrhosis. There are a lot of complications of cirrhosis, but the most dreaded one is hepatocellular carcinoma. I am going to do a brief review of cirrhosis and then I will talk about the HCC that is the focus of this review.